Experiments on centralized school choice and college admissions: a survey - Rustamdjan Hakimov; Dorothea Kübler (Experimental Economics, 2021)
The paper surveys the experimental literature on centralized matching markets, covering school choice and college admissions models. In the school choice model, one side of the market (schools) is not strategic, and rules (priorities) guide the acceptance decisions. The model covers applications such as school choice programs, centralized university admissions in many countries, and the centralized assignment of teachers to schools. In the college admissions model, both sides of the market are strategic. It applies to college and university admissions in countries where universities can select students, and centralized labor markets such as the assignment of doctors to hospitals. The survey discusses, among other things, the comparison of various centralized mechanisms, the optimality of participants' strategies, learning by applicants and their behavioral biases, as well as the role of communication, information, and advice. The main experimental findings considered in the survey concern truth-telling and strategic manipulations by the agents, as well as the stability and efficiency of the matching outcome.
Keywords: C92; D47; D83; 300; experiments; matching markets; school choice; college admissions; survey